From Informatica Umanistica to Digital Humanities and return: a conceptual history of Italian DH - Ciotti, Fabio (Testo e Senso, 2018)
This article traces a history of the Italian tradition in DH, concentrating in particular in the so-called Roman school, whose intellectual and methodological legacy is, in my view, particularly relevant in this historical moment. Usual historiographical accounts of DH indicate in the figure of Father Busa the initiator of the field. However, the work of father Busa was not at all isolated in Italy. Since the 50s and 60s of the last century the Italian "proto-DH" landscape has been very lively. But it is especially in the 80's that, thanks to Tito Orlandi and his group, a new domain of scholarship called “Informatica Umanistica” emerges and consolidates. The peculiarity of this tradition resides in its mainly theoretical and methodological view of the intersection between computing and humanities. Hence the relevance given to the foundational issues of formalization, modeling and encoding and the thoughtful consideration of the foundations of computation (Turing machine, formal languages, logic and classical Artificial Intelligence). The divergence between this view of DH and the "Big tent" approach mainstream in Anglo-American (and then global) tradition is evident. My position is that, even if the inclusive stance has been fruitful in the phase of the expansion, there is now the need for tracing both the internal and external borders of the DH field, and that the Italian tradition can give a substantial contribution in this endeavor.